Antiretroviral Therapy in the Clinic - Tsibris, Athe M. N. (American Society for Microbiology (ASM), 2010)
Antiretroviral therapy in the developed world has resulted in substantial reductions in HIV-associated morbidity and mortality, changing an HIV diagnosis from a likely death sentence into a manageable chronic infection (F. J. Palella, Jr., K. M. Delaney, A. C. Moorman, M. O. Loveless, J. Fuhrer, G. A. Satten, D. J. Aschman, and S. D. Holmberg, N. Engl. J. Med. 338:853-860, 1998). Several million years of life have been saved by effective anti-HIV treatment, although these successes should not obscure the magnitude of the ongoing worldwide HIV epidemic (R. P. Walensky, A. D. Paltiel, E. Losina, L. M. Mercincavage, B. R. Schackman, P. E. Sax, M. C. Weinstein, and K. A. Freedberg, J. Infect. Dis. 194:11-19, 2006). Readers of the Journal of Virology are doubtless aware of the fundamental advances in retrovirology that have made possible the development of potent inhibitors of HIV replication. In this review, we focus on the issues surrounding how these drugs and drug regimens are actually used in clinical settings. Their proper use requires detailed knowledge of the natural history of HIV infection, the pharmacology of the individual drugs, the complexities of drug-drug interactions, and the use of sophisticated molecular tests for monitoring of viral load, immunologic response, and drug resistance.